2019
DOI: 10.1016/j.omtn.2019.06.003
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: LINC00472 Acts as a Tumor Suppressor in NSCLC through KLLN-Mediated p53-Signaling Pathway via MicroRNA-149-3p and MicroRNA-4270

Abstract: Long non-coding RNAs and microRNAs (miRNAs) have been reported to participate in the progression of non-small-cell lung cancer (NSCLC). Long intergenic non-protein-coding RNA 472 (LINC00472), miR-149-3p, and miR-4270 were found to be involved in tumor activities, suggesting potential roles in NSCLC. Thus, this study aimed to examine the ability of LINC00472 to influence the progression of NSCLC with the involvement of miR-149-3p and miR-4270. Initially, differentially expressed long non-coding RNAs (lncRNAs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…In addition, in the present study, MEG3 regulated the NF-κB signaling pathway in HBE cells by targeting miR-149-3p. It has been reported that miR-149-3p is involved in the Akt1 signaling pathway in pancreatic cancer ( 40 ) and in the p53-signaling pathway in non-small-cell lung cancer ( 41 ). Future studies should focus on whether the regulatory effects of MEG3/miR-149-3p in COPD may be mediated by other signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the present study, MEG3 regulated the NF-κB signaling pathway in HBE cells by targeting miR-149-3p. It has been reported that miR-149-3p is involved in the Akt1 signaling pathway in pancreatic cancer ( 40 ) and in the p53-signaling pathway in non-small-cell lung cancer ( 41 ). Future studies should focus on whether the regulatory effects of MEG3/miR-149-3p in COPD may be mediated by other signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, miR-149-5p and miR-149-3p exhibit diverse roles in cancer progression. For example, long intergenic non-protein-coding RNA 472 inhibited tumor growth and metastasis by sponging and decreasing miR-149-3p expression, leading to the upregulation of KLLN and activation of p53 signaling in non-small cell lung cancer (NSCLC) cells, which suggested an oncogenic function of miR-149-3p ( 25 ). Conversely, miR-149-5p acted as a tumor suppressor in NSCLC ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zou et al identified that LINC00472 upregulation prevents the cell invasion, metastasis, and growth in NCI‐H1299 Cells. They also demonstrated that the upregulation of LINC00472 activates the p53‐signaling pathway, decreases cell invasion and metastasis in H1299 cell line via sponging miR‐4270 and miR‐149‐3p 77 …”
Section: Crndementioning
confidence: 95%
“…They also demonstrated that the upregulation of LINC00472 activates the p53-signaling pathway, decreases cell invasion and metastasis in H1299 cell line via sponging miR-4270 and miR-149-3p . 77…”
Section: Linc00472mentioning
confidence: 99%